Analisis Total Quality Management (TQM) terhadap Kinerja Karyawan pada UMKM Kepiting Soka di Pangkalan Batu - Harum Anisa; Siti Hasanah; Fitriyani Zebua; Irwan Nopian Sinaga (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the implementation of Total Quality Management (TQM) and its influence on employee performance at the Kepiting Soka Micro, Small, and Medium Enterprise (MSME) in Pangkalan Batu, Langkat Regency. This MSME operates in the soft-shell crab processing sector and faces challenges in maintaining product quality and production efficiency. The research uses a qualitative descriptive method, with data collection techniques including observation, interviews, and documentation. The results show that TQM implementation remains informal and unstructured. Although work practices such as precision and compliance with instructions reflect basic TQM principles, employee understanding of the concept is limited. Employee involvement in quality evaluation is also minimal, and there is no documented quality management system in place. The main obstacles In applying TQM in this MSME include a lack of training, limited resources, and the absence of clear Standard Operating Procedures (SOPs). Therefore, a gradual implementation of TQM is necessary, starting with the development of SOPs, regular training, and strengthening commitment to quality. These steps are expected to improve employee performance and enhance the competitiveness of The product in the market.